Prognostic biomarkers for immunotherapy with ipilimumab in metastatic melanoma. (21st March 2019) - Nyakas, M; Aamdal, E; Jacobsen, K D; Guren, T K; Aamdal, S; Hagene, K T; Brunsvig, P; Yndestad, A; Halvorsen, B; Tasken, K A; Aukrust, P; Mælandsmo, G M; et al.
Summary: New therapies, including the anti-cytotoxic T lymphocyte antigen (CTLA)-4 antibody, ipilimumab, is approved for metastatic melanoma. Prognostic biomarkers need to be identified, because the treatment has serious side effects. Serum samples were obtained before and during treatment from 56 patients with metastatic or unresectable malignant melanoma, receiving treatment with ipilimumab in a national Phase IV study (NCT0268196). Expression of a panel of 17 inflammatory-related markers reflecting different pathways including extracellular matrix remodeling and fibrosis, vascular inflammation and monocyte/macrophage activation were measured at baseline and the second and/or third course of treatment with ipilimumab. Six candidate proteins [endostatin, osteoprotegerin (OPG), C-reactive protein (CRP), pulmonary and activation-regulated chemokine (PARC), growth differentiation factor 15 (GDF15) and galectin-3 binding-protein (Gal3BP)] were persistently higher in non-survivors. In particular, high Gal3BP and endostatin levels were also independently associated with poor 2-year survival after adjusting for lactate dehydrogenase, M-stage and number of organs affected. A 1 standard deviation increase in endostatin gave 1·74 times [95% confidence interval (CI) = 1·10–2·78, P = 0·019] and for Gal3BP 1·52 times (95% CI = 1·01–2·29, P = 0·047) higher risk of death in the adjusted model. Endostatin and Gal3BP may represent prognostic biomarkers for patients on ipilimumab treatment in metastatic melanoma and should be further evaluated. Owing to the non-placebo design, we could only relate our findings to prognosis during ipilimumab treatment. Graphical Abstract: